Ideology, strategy, and party change spatial analyses of post-war election programmes in 19 democracies - Budge, Ian; Robertson, David 1946-; Hearl, Derek (Cambridge University Press, 1987)
The relevance of this book to central concerns of political and social science hardly needs emphasizing. Parties are the organizing force of democratic governments, giving coherence and direction to their policies and relating them to popular preferences. Election programmes are crucial to this role, providing electors with some insight into the policies they are voting for, and parties themselves with a starting point for their activity in government. Discussion begins with a comparative assessment of the impact of election pledges on government action. The book goes on to describe systematically the place of the programmes in the political process of nineteen democracies. It subjects them to detailed qualitative, quantitative and spatial analyses to answer such questions as: Who prepares election programmes and how? What is the nature of modern party divisions? Do they differ across countries? Is there indeed an 'end of ideology' or an intensification? Does the need to attract votes weaken old partisan attachments? Combining individual studies of each country with comparative analyses on a scale never previously undertaken, the book will interest country specialists and comparativists and prove indispensable to research on voting and party behaviour, coalition formation, ideology, and rational choice